Advanced Green Thermoset Resin Tailored for Nanocellulose‐Based Filament‐Reinforced Polymer Composite and Sustainable Development. (9th November 2022) - Agumba, Dickens O.; Panicker, Pooja S.; Pham, Duc Hoa; Kim, Jaehwan
Abstract: White pollution has caused extensive damage to the environment, thus making sustainable development necessary. Bioresources such as starch and cellulose are attractive candidates for sustainable materials. Despite the enticing aspects, engineering high‐performance materials from starch and cellulose have not been feasible due to the suboptimal performance of the final products. Here, this work reports a high‐strength and all‐green resin synthesized from low‐cost and abundant sustainable resources of starch, citric acid (CA), and lignin through esterification. The resulting resin discloses a record high strength (158.79 ± 6.51 MPa) and toughness (6.26 ± 0.39 MJ m −3 ), well above the existing starch‐based and epoxy resins. The adhesion strength (23.94 ± 1.092 MPa) of the resin to cellulose film highlights its feasibility in developing high‐performance cellulose‐reinforced polymer composite. A nanocellulose‐based long filament is manufactured via wet‐spinning on a continuous rapid fiber production system and knit into mats to ascertain the hypothesis. By integrating the resin into nanocellulose‐based filament mats through hand‐layup, hot‐pressing, and postcuring, an all‐green composite is conceived with excellent flexural strength (315.9 ± 20.1 MPa) and stiffness (34.4 ± 1.16 MPa). The high‐strength and all‐green resin can be used in natural fiber composites for automotive, packaging, and optics. Abstract : This work demonstrates that robust biocomposites outperforming common synthetic materials can be fabricated by combining bioderived resin and nanocellulose‐based long filaments. A high‐strength and all‐green resin is synthesized from sustainable resources of starch, citric acid, and lignin through esterification. The resin offers an excellent interfacial strength to cellulose, while the reinforcement by the fibers allows for high mechanical properties.